Unit Trust Scheme by Bumiputras in Sabah / Dg. Ku Sarahwati Pg. Talib - Pg. Talib, Dg.Ku Sarahwati (1997)
Unit Trust forms a very important investment in many countries. Although it is almost forty years to date since Unit Trust was first introduced in Malaysia by a group of British investors, however the participation level by Bumiputras is still low. Therefore, in this study I shall stress on the investors' people's and Unit Trust Fund managers' problems, ways of how to solve the problems and how the Unit Trust Fund Managers gain the trust and confidence from the people.